2014
DOI: 10.15850/ijihs.v2n1.286
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Two-Layer Density Gradient and Three-Layer Density Gradient Technique for Sperm Preparation at Aster Fertility Clinic, Dr. Hasan Sadikin General Hospital

Abstract: Objective: To compare the efficacy of sperm preparation techniques modified by two layer density gradient technique (80%, 40%). Methods: Sperm preparation was performed by two-and three-layer density gradient technique by centrifugation at 500 rpm for 20 minutes using SpermGrad (Vitrolife, Sweden). Results: The average concentration of total sperm preparation by two-layer density gradient was 23.19 million with a standard deviation of 11.9 million while the result of three-layer density gradient preparation ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(11 reference statements)
0
2
1
Order By: Relevance
“…The pellet is then re-suspended with gradient media again in DGC technique with and without TAD 600mg Glutathione, so spermatozoa migrate through density of media and then from pellet to upper media, the data of this study showed increase concentration rate of sperm was in DGC with TAD 600mg Glutathione technique. These results were in contrast with other studies using DGC techniques compared with other techniques (12).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The pellet is then re-suspended with gradient media again in DGC technique with and without TAD 600mg Glutathione, so spermatozoa migrate through density of media and then from pellet to upper media, the data of this study showed increase concentration rate of sperm was in DGC with TAD 600mg Glutathione technique. These results were in contrast with other studies using DGC techniques compared with other techniques (12).…”
Section: Discussioncontrasting
confidence: 99%
“…Density gradient centrifugation technique used for the separation of sperms has been golden technique In a lot of ART's laboratories because of its performance that are easily and quickly resulting in highly quality of sperm motility (8).…”
Section: -Discontinuous Density Gradient Centrifugation (Dgc) Technimentioning
confidence: 99%
“…The importance of sperm preparation techniques in ART's, is to obtain the highest sperm recovery and in vitro treatment of spermatozoa to improve their function like, motility and improve or maintain the functional capacity for successful fertilization through supplementation of protective media (15) .…”
Section: Discussion:-mentioning
confidence: 99%